2022
DOI: 10.3390/ijerph191710911
|View full text |Cite
|
Sign up to set email alerts
|

Promotion of Food and Beverages by German-Speaking Influencers Popular with Adolescents on TikTok, YouTube and Instagram

Abstract: The promotion of nutritionally poor food and beverages (F&B) has a proven effect on children’s eating preferences and, therefore, plays a significant role in today’s childhood obesity epidemic. This study’s objective was to assess the prevalence (exposure) and context (power) of the F&B cues in influencer content across three platforms: TikTok, YouTube, and Instagram. The selected influencers were popular with adolescents, with a combined total of more than 34 million followers/subscribers. We employed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 45 publications
3
12
0
Order By: Relevance
“…Food advertisements and, later, food influencers have also been criticized for negatively influencing food consumption by favoring unhealthy choices and snacking (Beuckels & De Jans, 2022;Coates et al, 2019;Mc Carthy et al, 2022;Smith et al, 2019). Research has suggested that unhealthy foods appear more often and receive more positive reactions on social media than alternative healthy content (Alruwaily et al, 2020;Beuckels & De Jans, 2022;Winzer et al, 2022).…”
Section: Social Media Influencers and Their Criticismmentioning
confidence: 99%
See 2 more Smart Citations
“…Food advertisements and, later, food influencers have also been criticized for negatively influencing food consumption by favoring unhealthy choices and snacking (Beuckels & De Jans, 2022;Coates et al, 2019;Mc Carthy et al, 2022;Smith et al, 2019). Research has suggested that unhealthy foods appear more often and receive more positive reactions on social media than alternative healthy content (Alruwaily et al, 2020;Beuckels & De Jans, 2022;Winzer et al, 2022).…”
Section: Social Media Influencers and Their Criticismmentioning
confidence: 99%
“…Food advertisements and, later, food influencers have also been criticized for negatively influencing food consumption by favoring unhealthy choices and snacking (Beuckels & De Jans, 2022; Coates et al, 2019; Mc Carthy et al, 2022; Smith et al, 2019). Research has suggested that unhealthy foods appear more often and receive more positive reactions on social media than alternative healthy content (Alruwaily et al, 2020; Beuckels & De Jans, 2022; Winzer et al, 2022). However, we discovered that many of the aforementioned studies focused on children, who are neither the target audience of many influencers nor common social network users (e.g., Facebook and Instagram users should be older than 13 years to create a profile).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to being the source of entertainment and recreation, short videos play an essential role in the education [ 9 , 10 ], and health industries [ 11 , 12 ] as well. Short videos also promote food and beverages [ 13 ]. As a result of the numerous advantages and excessive consumption of short-form content, the joint photographic experts’ group (JPEG) experts developed an image-rich content-based international standard called JPEG Snack [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…92% of food advertisements encountered by children in digital and television platforms in Germany are for less healthy products such as fast food, snacks, or sweets [2]. More recently, social media and influencer-based marketing campaigns have emerged as influential channels [3]. There is strong direct and indirect evidence that exposure to marketing of unhealthy foods is associated with an increased risk for childhood overweight and obesity [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%